Design Thinking for Teaching Creativity in the University. A feasibility project - de Miguel Zamora, Marta (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2021)
Design Thinking methodology focuses on analyzing something in order to implement changes or improvements. It is an innovation process and, as such, a pattern of applied creativity. Many organizations of different kinds, including schools, have implemented this philosophy in their centers and have disseminated its methods. Its main characteristic is to foster new ways of thinking and to face problems, which is why we consider that this methodology can be useful in the classroom. With the aim of integrating Design Thinking into the teaching exercise of Advertising Creativity at the university level, we propose a feasibility proyect that involves the design of a didactic program and the analysis of its viability. Previously, we have studied the situation in which the teaching of Creativity is found in the branch of Communication Sciences. This study has given us indications of improvement in teaching and specific objectives that have been covered with the design of a teaching planning. The viability analysis has been favorable from the didactic, material, human and economic perspectives, which enables the possibility of its practical execution.